2021
DOI: 10.7554/elife.70269
|View full text |Cite
|
Sign up to set email alerts
|

Electron cryo-tomography reveals the subcellular architecture of growing axons in human brain organoids

Abstract: During brain development, axons must extend over great distances in a relatively short amount of time. How the subcellular architecture of the growing axon sustains the requirements for such rapid build-up of cellular constituents has remained elusive. Human axons have been particularly poorly accessible to imaging at high resolution in a near-native context. Here, we present a method that combines cryo-correlative light microscopy and electron tomography with human cerebral organoid technology to visualize gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 78 publications
(106 reference statements)
3
15
1
Order By: Relevance
“…2 D ). Similar to previous cryo-ET studies of mammalian axons ( Hoffmann et al, 2021 ; Lučić et al, 2007 ; Schrod et al, 2018 ), the observed actin filaments ran roughly parallel to the MT network rather than forming rings around the axon shaft. This actin may correspond to “deep” actin, which is dynamic and transported slowly through axons ( Ganguly et al, 2015 ).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…2 D ). Similar to previous cryo-ET studies of mammalian axons ( Hoffmann et al, 2021 ; Lučić et al, 2007 ; Schrod et al, 2018 ), the observed actin filaments ran roughly parallel to the MT network rather than forming rings around the axon shaft. This actin may correspond to “deep” actin, which is dynamic and transported slowly through axons ( Ganguly et al, 2015 ).…”
Section: Resultssupporting
confidence: 86%
“…We did not observe the actin/spectrin membrane-associated periodic skeleton, which forms a sheath under the axonal plasma membrane (He et al, 2016;Xu et al, 2013). The membrane-associated periodic skeleton was also not detected in previous cryo-ET studies of mammalian neurons (Fischer et al, 2018;Hoffmann et al, 2021;Lučić et al, 2007;Schrod et al, 2018;Tao et al, 2018a). We speculate it may be excluded from the very thin regions targeted in this study.…”
Section: Cytoskeletal Filaments In the Mammalian Axoplasmcontrasting
confidence: 70%
See 1 more Smart Citation
“…We use neuronal markers SMI312 to identify axons and MAP2 to identify dendrites ( Hoffmann et al., 2021 ). However, other markers may also be used.…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…Other examples of such cryo-ET approaches are studies concerning axon growth. Quantification of the endoplasmic reticulum in the growing shaft correlates with scarcity of ribosomes suggesting the high demand for lipid biosynthesis while low translational competence during growth ( Hoffmann et al, 2021 ). Furthermore, the quantitative analysis of cytoskeletal elements found that the endoplasmic reticulum is tethered to microtubules through short linkers in the axons ( Foster et al, 2021 ).…”
Section: Quantitative Cryo-electron Tomographymentioning
confidence: 99%